Numerical Investigation of "Frog-Leap" Mechanisms of Three Particles Aligned Moving in an Inclined Channel Flow (Advances in Applied Mathematics and Mechanics, 2018)
Intrigued by our recent experimental work (H. Yamaguchi and X. D. Niu,J. Fluids Eng., 133 (2011), 041302), the present study numerically investigate theflow-structure interactions (FSI) of three rigid circular particles aligned moving inan inclined channel flow at intermediate Reynolds numbers by using a momentum-exchangedimmersed boundary-lattice Boltzmann method. A "frog-leap" phenomenonobserved in the experiment is successfully captured by the present simulation and flowcharacteristics and underlying FSI mechanisms of it are explored by examining the effectsof the channel inclined angles and Reynolds numbers. It is found that the asymmetricdifference of the vorticity distributions on the particle surface is the main causeof the "frog-leap" when particle moves in the boundary layer near the lower channelboundary.